1999
DOI: 10.1103/physreve.60.6480
|View full text |Cite
|
Sign up to set email alerts
|

Single-vehicle data of highway traffic: A statistical analysis

Abstract: In the present paper, single-vehicle data of highway traffic are analyzed in great detail. By using the single-vehicle data directly, empirical time headway distributions and speed-distance relations can be established. Both quantities yield relevant information about the microscopic states. Several fundamental diagrams are also presented, which are based on time-averaged quantities and compared with earlier empirical investigations. In the remaining part, time-series analyses of the averaged as well as the si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
242
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(264 citation statements)
references
References 26 publications
19
242
1
Order By: Relevance
“…Both, theoretical [5,6,7] and empirical [8,9,10,11,12,13,14,15,16,17] studies indicate that the phenomenology of congested traffic is more complex than originally expected. There seems to be a rich spectrum of traffic states [5,6,12,13], hysteretic or continuous temporal or spatial transitions among them [7,11,12,13,18,19], and fluctuations or a erratically appearing dynamics play a significant role [13,16,20,21,22]. In order to make sense out of this, it is increasingly important to have suitable ways of data processing, in order to extract the information relevant for scientific investigations or specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…Both, theoretical [5,6,7] and empirical [8,9,10,11,12,13,14,15,16,17] studies indicate that the phenomenology of congested traffic is more complex than originally expected. There seems to be a rich spectrum of traffic states [5,6,12,13], hysteretic or continuous temporal or spatial transitions among them [7,11,12,13,18,19], and fluctuations or a erratically appearing dynamics play a significant role [13,16,20,21,22]. In order to make sense out of this, it is increasingly important to have suitable ways of data processing, in order to extract the information relevant for scientific investigations or specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…This location has the unique characteristic that, although the flow of traffic is high, traffic jams are very sporadically seen. In this sense it is a unique measurement point to gather experimental facts to understand the microscopic structures in synchronized traffic states [1], which was not reported outside of Germany yet.…”
Section: Measurement Analysis Architecturementioning
confidence: 99%
“…Recent studies have shown very complex structures in the traffic flow [1]. This state is called the synchronized state, which has to be distinguished from a free flowing and congested state.…”
Section: Introductionmentioning
confidence: 99%
“…For both lanes, longitudinal velocity (standard deviation (SD) of 8.3 km/h) was modeled based on available data from instrumented vehicles. The distance separation of the lead vehicles was based on a THW density distribution, with a mean THW of 1.15 s, based on [13]. Lateral-positioning behavior (swerving) of the traffic was created according to a model based on available lanekeeping data (SD of 0.30 m).…”
Section: Experimental Design and Procedurementioning
confidence: 99%